Quantification of biomass in a biooxidation system - Moon, Jo-Ann Helen (Centre for Bioprocess Engineering Research, 2017)
[PAGE 1 missing] The aim of this study was to investigate and compare various methods to enumerate the number of bacteria in a minerals biooxidation system. In this system most of the bacteria are attached to fine particles of ore and therefore cannot be enumerated by direct cell counting. This has hindered attempts to understand the mechanism by which the bacteria assist in the leaching process. The methods reported in the literature to enumerate both the free and attached bacteria in a biooxidation system can be divided into 2 categories: direct methods and indirect methods. The direct methods involve the quantification of the bacteria by direct observation. It is difficult to enumerate attached bacteria by direct observation but attempts have been made to desorb or dislodge these bacteria. Such experiments have had limited success in achieving dislodgement of all the attached bacteria. However, the results have shown that desorption of the bacteria from the mineral surface is possible. Indirect methods involve the monitoring of a cell component such as protein, nitrogen and carbon. Biomass concentrations have been estimated using its metabolic activity by means of a maximum specific oxygen utilisation rate. The purpose of this study was to compare the various methods and test their suitability to the quantification of biomass in a biooxidation system. In particular the biooxidation system investigated treated an arsenopyrite-pyrite concentrate from Fairview Gold Mine, Barberton, South Africa. The elemental analysis of the concentrate is 5.84% arsenic, 21.71 % sulphur,24.01 % iron and 1.41 % carbon. The dominant bacteria present in the biooxidation system were Leptospirillum ferrooxidans and Thiobacillus thiooxidans as shown by 16S rDNA analysis. The methods investigated are microscopic counting, gravimetric dry weight determination, desorption, determination of chemical oxygen demand, ashing, protein analysis, nitrogen analysis, total organic carbon analysis and measurement of oxygen utilisation rate. The oxygen utilisation rate method differs from the other methods as it uses the metabolic activity of the bacteria to measure the bacterial concentrations.